Constantinople through the Ages : The Visible City from Its Foundation to Contemporary Istanbul - Burgersdijk, Diederik,; Gerritsen, Fokke,; Waal, Willemijn, (Classical Studies E-Books Online, Collection 2024., 2025)
Constantinople Through the Ages aims to map the long and rich history of Constantinople, from its foundations to the present. Starting point is the 'visible city'; the ways in which continuity and change in history are still observable in present-day Istanbul. The contributors, each of them foremost experts in their fields, address the interaction between the different layers of time from various sources and perspectives. They explore how later inhabitants received and appropriated the legacy of their predecessors, and how the city's tangible and intangible heritage has been perceived and (ab)used in both the past and the present. See Less